Determinant of bond market in Malaysia / Shamsul Arif Zulfikar Husni - Zulfikar Husni, Shamsul Arif (2022)
The Malaysian bond market has experienced fast growth in recent years as more business operations have increased from time to time. However, only a few people are well aware of the macroeconomic factors that significantly impact the bond performance specifically bond yields. The issue arises when there are only a few researchers conduct studies related to government bond yields and it is rare to find any research conducted in Malaysia. Thus, to cater that problem, this study was conducted to determine the relationship between government bond yields and macroeconomic factors such as gold price, oil price, and stock market performance. This study will also identify the most significant variables towards the government bond yields as to improve the confident of government and investors in making any further investment decision. Secondary data were obtained from 2006 to 2020, including quarterly data used in this paper that also accumulate to 60 number of observations. Moreover, the study's findings are divided into three categories: descriptive analysis, correlation analysis, and regression analysis. The expected result for this study is that only gold price and crude oil price shows a significant relationship between Malaysia government bond yields. These empirical findings assist investors in determining the elements that may influence government bond yields and decision-making.